An electrochemical biosensor based on conductive colloid particles self‐assembled from poly(3‐thiophenecarboxylic acid) and chitosan. Issue 46 (23rd September 2018) - Zhang, R.; Wang, L.; Zhang, C.; Yang, R.; Sun, X.; Song, B.; Wong, C.‐P.; Xu, Y.
ABSTRACT: A novel kind of conductive self‐assembled colloid particles (CPs) was prepared from poly(3‐thiophenecarboxylic acid) (PTPCA) and chitosan (CS) via electrostatic interaction and π–π interaction. The resultant CPs were then cast on the electrode surface to provide a platform for fabricating high‐sensitive biosensor. It should be noted that the good conductivity of PTPCA can accelerate the electron transfer and facilitate the signal transduction from the CP film to the underlying electrode. This advantage endowed the biosensor with high sensitivity for H2 O2 detection. Under the optimal conditions, a linear range from 1 × 10 −11 to 1 × 10 −5 mol L −1 with a detection limit of 3 × 10 −12 mol L −1 was obtained for H2 O2 detection. The biosensor can be used to detect H2 O2 in commercial disinfector with satisfactory results. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46764. Abstract :